USING NON-INVASIVE METHODS FOR EVALUATING MYOCARDIAL ISCHEMIA IN ASSESSMENT OF THE FUNCTIONAL SIGNIFICANCE OF INTERMEDIATE CORONARY ARTERY STENOSES IN PATIENTS WITH CHRONIC ISCHEMIC HEART DISEASE - D. I. Darenskiy; V. V. Gramovich; E. A. Zharova (Евразийский Кардиологический Журнал, 2016)
Key points of using non-invasive methods for evaluating myocardial ischemia (exercise electrocardiogram, stress echocardiography, single photon emission computed tomography and myocardial perfusion imaging with stress-test) in clinical practice to determine the functional significance of intermediate coronary artery stenoses (50-70% of the vascular lumen) are discussed in the review.